Crushing investigation of crash boxes filled with honeycomb and re-entrant (auxetic) lattices. (May 2020) - Simpson, Jonathan; Kazancı, Zafer
Abstract: This study investigates the crush response of lattice filled square tubes under quasi-static compressive loading. Auxetic lattice (auxetic strut and re-entrant) filled tubes have been compared to a non-auxetic (honeycomb) filled alternative and an empty tube. All structural lattices within this study were designed to be of equal mass. The experimental results were computationally validated using Abaqus®/Explicit. Experimental and numerical results show good agreement which highlights that the addition of lattice structures greatly improved the crashworthiness performance of the crash tube compared with an empty tube. By comparing the experimental values of energy absorption (EA), through the inclusion of a filler lattice a 62.6%, 64.0% and 79.1% increase over the empty tube were obtained for the auxetic strut, re-entrant and honeycomb structures respectively. Highlights: The performances of various square lattice filled tubes against empty tubes under quasi-static compressive loading are investigated. The energy absorption performance of the crash tubes could be improved by filling lattice structures. The effects of incorporating auxetic and conventional lattice structures inside a thin-walled tube assessed. A numerical model was established to further develop the concepts and results observed from the experimental study.